2021
DOI: 10.3390/jcm10122734
|View full text |Cite
|
Sign up to set email alerts
|

Corticosteroid Resistance in Smokers—A Substudy Analysis of the CORTICO-COP Randomised Controlled Trial

Abstract: The CORTICO-COP trial showed that eosinophil-guided corticosteroid-sparing treatment for acute exacerbation of chronic obstructive pulmonary disease was non-inferior to standard of care and decreased the accumulated dose of systemic corticosteroids that patients were exposed to by approximately 60%. Smoking status has been shown to affect corticosteroid responsiveness. This post hoc analysis investigated whether eosinophil-guided treatment is non-inferior to conventional treatment in current smokers. The main … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 32 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…Another real-world observational study conducted in 1290 Chinese patients admitted for AECOPD found that the hospitalisation time following treatment with systemic corticosteroids was shorter in patients with eosinophilia than patients without eosinophilia with smoking history (median 8 vs 9 days, p=0.046), and the results were similar between the two groups in patients without smoking history (p=0.376) 41. Another substudy analysis of the Corticosteroid Reduction in COPD (CORTICO-COP) RCT showed that smoking status did not influence the role of eosinophils as a biomarker in guiding corticosteroid treatment 19. However, the small sample size (n=318) may have been insufficient to power the statistical analysis.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Another real-world observational study conducted in 1290 Chinese patients admitted for AECOPD found that the hospitalisation time following treatment with systemic corticosteroids was shorter in patients with eosinophilia than patients without eosinophilia with smoking history (median 8 vs 9 days, p=0.046), and the results were similar between the two groups in patients without smoking history (p=0.376) 41. Another substudy analysis of the Corticosteroid Reduction in COPD (CORTICO-COP) RCT showed that smoking status did not influence the role of eosinophils as a biomarker in guiding corticosteroid treatment 19. However, the small sample size (n=318) may have been insufficient to power the statistical analysis.…”
Section: Discussionmentioning
confidence: 97%
“…41 Another substudy analysis of the Corticosteroid Reduction in COPD (CORTICO-COP) RCT showed that smoking status did not influence the role of eosinophils as a biomarker in guiding corticosteroid treatment. 19 However, the small sample size (n=318) may have been insufficient to power the statistical analysis. Similarly, our study based on a real-world setting observed that regardless of smoking, higher levels of eosinophils reduced the risk of corticosteroid treatment failure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations